250 Safe and sound for performance's sake? An exploration on health and safety awareness in elite rugby. (3rd March 2020) - Chen, Yanbing; Buggy, Conor; Kelly, Seamus
Abstract : Background: In elite rugby union, players often expose themselves to risk-taking behaviours resulting in a high risk acceptance level. The practical and theoretical occupational safety and health (OSH) have the potential to reflect health outcomes (e.g., injuries and accidents) in sports settings. Objective: This study explores key indicators of injury prevention and welfare protection in rugby union from an OSH perspective. Design: This study utilises semi-structured interview, the duration of which ranged from 22 to 50 minutes digitally recorded with consents. Setting: Individual interviews were conducted with current rugby supporting staff involving in national, provincial and university level. Patients (or Participants): The participants (n=15) were current rugby supporting staff including coaching staff, medical staff and other management personnel. Interventions (or assessment of risk factors): The interview transcripts were inductively analysed by using Nvivo software, the key risk factors were then identified using abductive analysis by adopting an existing safety climate framework. Main outcome measurements: Factors being neglected in sports research will be discussed in this study, for example, safety justice is relating to players' risk-taking behaviours during match or training; whether opponents are 'co-workers' and players' safety attitudes towards co-workers can influence players' aggressiveness which relates to injuries and accidents. Results: The framework identified for evaluating OSH awareness will be presented from two dimensions including five themes: rugby management commitment (management safety priority, management safety empowerment and management safety justice) and rugby player involvement (players' safety priority and players' trust in co-workers' safety competence). Conclusions: The findings have theoretical implications for rugby organisations to design a survey to facilitate the development of appropriate behaviour interventions. Furthermore, the framework could be potentially applied in wider sports settings.